Legged robots at MIT what's new since Raibert?. - Pratt, G.A.
The MIT Leg Lab is best known for the seminal work of Marc Raibert, who showed in the 1980s that robotic running could be accomplished using a few simple, decoupled control laws. Raibert had shown how to calculate the control effort required for the next step of a run based on the results of the previous step, using simple physics-based rules. But smoothly controlling joints in a continuous-time fashion to effect walking seemed more difficult, particularly for non-stead state conditions. It was unclear how to combine passive dynamics with active control. Other researchers were beginning to address robot walking, and the rich diversity of their approaches was very exciting. It thus seemed that walking was the next important area. We embarked on a two-pronged approach: one focusing on making improvements to electromechanical actuators and robot design, the other on walking algorithms and control
Keywords: MIT Leg Lab; Active control; Control algorithms; Dynamics; Electromechanical actuators; Legged locomotion; Mobile robots; Walking robots